Efforts to Improve Lower Passing Learning Outcomes Through the Volleyball Game Demonstration Method in Class XI Students of SMAN 1 Pangkalan Kerinci: Upaya Meningkatkan Hasil Belajar Passing Bawah Melalui Metode Demostrasi Permainan Bola Voli pada Siswa Kelas XI SMAN 1 Pangkalan Kerinci - Ambar Mufidah; Daharis Daharis (Badnur Medisa Group, 2023)
This study aims to determine the increase in passing under the volleyball game using the demonstration method in class XI students of Senior High School 1 Pangkalan Kerinci. This type of research is classroom action research (PTK) which is taken in two cycles. The subject of this research was carried out in class XI of Senior High School 1 Pangkalan Kerinci with a total of 35 students. The data collection for this research was obtained through practice tests to see an increase in students' lower passing skills. The results of this study indicate that the use of the demonstration method in Physical Education and Recreation learning can improve students' learning skills in the basic technique of passing under volleyball for class XI Senior High School 1 Pangkalan Kerinci. This can be seen from the number of students who completed in cycle I as many as 18 students with a completeness percentage of 51% and the incomplete score was 17 students with a percentage of 49% the average value was 70 and increased in cycle II, namely students who completed as many as 30 students with a completeness percentage of 86% and the incomplete score was 5 students with a percentage of 14% with an average score of 80. Based on the results of the study it can be concluded that the research can be concluded that research using the demonstration method in Physical Education learning can improve passing that the volleyball game of class XI students of Senior High School 1 Pangkalan Kerinci.